Yield comparison of simulated rainfed wheat and barley across Middle-East. (May 2017) - Schoppach, Rémy; Soltani, Afshin; Sinclair, Thomas R.; Sadok, Walid
Abstract: Rain-fed wheat and barley are key crops in the Middle-East. A slight improvement in the effective use of water and in grain yield could greatly improve lives of subsistence farmers. This study aimed to evaluate the relative merits of wheat and barley in this region by simulating yields across 404 uniformly spread locations across 30 growing seasons. The results emphasized the primary importance of sowing date in each location. In comparison to wheat, barley generally was capable of rapid progress through its development stages allowing it to avoid deleterious late-season droughts and to have greater yields in low rainfall regions. A large part of Middle-East appeared unsuited for rain-fed production of these two grain species if seasonal yield variability is a concern. Highlights: Wheat and barley yield simulations over 404 locations and 30 season in Middle-East. Sowing data had large impact on yield for both species. Relative yield advantage of wheat and barley varied with location. Much of area proved to be too arid for both species. Probability of achieving threshold yields important in species selection.